1998
DOI: 10.1038/sj.mp.4000388
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of D2 dopamine receptor expression

Abstract: The question of whether or not there is a polymorphism in or near DRD2 which is associated with receptor density remains unanswered. Both clinical and animal data demonstrate that D 2 dopamine receptor density is highly variable among individuals; differences of more than 100% are not uncommon. Among inbred mouse strains and F 2 intercrosses produced from these strains, it appears that most of the genetic variation in receptor expression is not associated with polymorphisms in or near Drd2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…This latter suggestion has been recently confirmed by Pohjalainen et al (1998), but was contradicted by Laruelle et al (1998). At the moment, it is still unclear whether or not the Al allele is associated with lower D 2 expression (Hitzemann, 1998). Since other reports of associations between the A2 allele and similar neuropsychiatric disorders are scarce, the association of the A2 allele in our sample is difficult to interpret.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…This latter suggestion has been recently confirmed by Pohjalainen et al (1998), but was contradicted by Laruelle et al (1998). At the moment, it is still unclear whether or not the Al allele is associated with lower D 2 expression (Hitzemann, 1998). Since other reports of associations between the A2 allele and similar neuropsychiatric disorders are scarce, the association of the A2 allele in our sample is difficult to interpret.…”
Section: Discussionmentioning
confidence: 44%
“…In addition, one might theorize that lower densities of the D 2 receptor in OCD patients are caused by genetic factors. The A1 allele of Taq I A polymorphism in the D 2 receptor (DRD2) gene locus has been suggested to be associated with reduced DRD2 receptor densities (Hitzemann, 1998;Jonsson et al, 1999). Data on the DRD2 TaqI A polymorphism in OCD are limited, but Nicolini et al found a higher frequency of the DRD2 TaqI A2 allele in a small subgroup of OCD patients (n = 12) with tics, when compared to controls (Nicolini et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…23 In their normal controls, however, the direction of the result was decreased binding potential for A1A2 genotypes vs A2A2 genotypes, as found by Pohjalainen et al (the rare A1A1 genotype could not be evaluated). In a review of both papers, 24 Hitzemann argued, based on data from mouse linkage studies of DRD2 receptorbinding potential, that the majority of variation in receptor density is due to genes that lie elsewhere from DRD2 in the genome, but that a polymorphism that affects receptor density also may exist in or near the mouse DRD2 gene.…”
mentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24] In inbred mice strains a genome-wide search for catalepsy-related genes using a quantitative trait loci approach detected a locus near or at the DRD2. 25 Therefore, also in humans several attempts have been performed searching for associations between dopamine D2 receptor polymorphisms and different measures of dopaminergic binding parameters or glucose metabolism in brain regions containing dopaminergic innervation (Table 1).…”
mentioning
confidence: 99%